China’s Cross Border Mergers and Acquisitions: Transaction Characteristics that Make Deal Complete - Huang, Junhao; Swatdikun, Trairong; Sahayrak, Kongkiat (Science, Technology, and Social Sciences Procedia, 2021)
M&A is a financial strategy that undoubtedly provides a good opportunity for business to renew its strategic position. Thus, exploring deal characteristics on a differ of deal completion is worth studying. This paper not only explore the transaction characteristics of China’s cross border M&A, but also examine the differ of deal characteristics on deal completion. Hypotheses were set up to test whether the deviation between the given characteristics and the deal completion are difference among the groups or not. It collects different characteristics of M&A in China from 2011 to 2021. The data associated with different characteristics includes target nation, deal purpose, deal attitude, deal size, deal year, target industry and form of transaction were obtained via Rifinitiv Eikon. Data analysis reveals that deal purpose and deal attitude are among the transaction characteristics that differ when deal completion were taking into consideration. This finding shed some light for financial consultant that difference purpose and attitude tend to move the deal into the completion differently. Thus, difference directions among purpose and attitude change their customer intention toward the deal, or revealing the expected result even before the transaction take place.